Review of amphipods of the family Pleustidae Buchholz, 1874 (Crustacea: Amphipoda) from the coastal waters of Sakhalin Island (Far East of Russia). I. Subfamily Neopleustinae Bousfield & Hendrycks, 1994 - Labay, Vjacheslav S. (Zootaxa, 2021)
Taxonomic analysis of the subfamily Neopleustinae Bousfield & Hendrycks, 1994, is performed. Cladistic analysis of morphological relationships within the genera Hendrycksopleustes gen. nov., Neopleustes Stebbing, 1906, and Shoemakeroides Hendrycks & Bousfield, 2004, is performed. A new genus Hendrycksopleustes gen. nov. is described. A review of the subfamily Neopleustinae from the shelf of Sakhalin Island and adjacent water area, based on all literature and own data, is provided. Based on new material, a new species Hendrycksopleustes neimanii sp. nov. is described from the shelf of Sakhalin Island. Status of the species Neopleustes euacanthus (G. Sars, 1877) is restored. New subspecies Neopleustes boecki pacifica ssp. nov. and Neopleustes pulchellus asiaticus ssp. nov. are described from the shelf of Sakhalin Island. Keys to the amphipod genera of the subfamily Neopleustinae and to the world species of the genera Neopleustes and Shoemakeroides are provided.